2015
DOI: 10.1145/2701425
|View full text |Cite
|
Sign up to set email alerts
|

Visual Enhancement of MR Angiography Images to Facilitate Planning of Arteriovenous Malformation Interventions

Abstract: The primary purpose of medical image visualization is to improve patient outcomes by facilitating the inspection, analysis, and interpretation of patient data. This is only possible if the users' perceptual and cognitive limitations are taken into account during every step of design, implementation, and evaluation of interactive displays. Visualization of medical images, if executed effectively and efficiently, can empower physicians to explore patient data rapidly and accurately with minimal cognitive effort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The purpose of medical‐image‐data visualization is to support “the inspection, analysis and interpretation of patient data” and, more specifically, to enable “physicians to explore patient data rapidly and accurately with minimal cognitive effort” [ABK*15]. Medical image data, such as CT and MRI, are physical measurements which exhibit noise and inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of medical‐image‐data visualization is to support “the inspection, analysis and interpretation of patient data” and, more specifically, to enable “physicians to explore patient data rapidly and accurately with minimal cognitive effort” [ABK*15]. Medical image data, such as CT and MRI, are physical measurements which exhibit noise and inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…Signal detection theory originated as a method of analysing experiments where auditory or visual stimuli have to be distinguished from some background noise. Since this initial use, it has been applied to the analysis of memory tasks, cognition as well as tasks within the medical domain [ABKP15].…”
Section: Signal Detection Theorymentioning
confidence: 99%
“…In [CWD*14], in contrast, for depth discrimination, tasks using simulated angiography‐like data sets stereoscopic displays proved more effective in most cases against 2D displays. Recently, [ABKP15] investigated methods to enhance MR angiography images by combining contour enhancement with stereopsis for DVR. Using a relative depth task, it was found that whilst stereopsis improved accuracy, it was most effective when combined with contour enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Both transparency based and importance-driven volume rendering were used to highlight spatial localization and temporal progression. Abhari et al [1] emphasized the importance of contour enhancement and stereopsis in visualizing vascular structures. Their study showed that volume rendering and a non-photorealistic shading of non-contrast-enhanced MRA based models increase the perception of continuity and depth.…”
Section: Introductionmentioning
confidence: 99%